A technique for developing CAD geometry of long bones using clinical CT data. Issue 11 (November 2015) - Davis, Matthew L.; Vavalle, Nicholas A.; Stitzel, Joel D.; Gayzik, F. Scott
Highlights: We present a technique to develop CAD representations of long bones from clinical CT data. A map of cortical thickness through the long axis of the bone is provided; regions of bone below the resolution of the CT scanner were developed from literature data. A continuous map of area moment of inertia for six long bones. The technique was applied to subjects representing three specific anthropometries. Abstract: Computed tomography scans are a valuable tool for developing computational models of bones. The objective of this study is to present a method to generate CAD representations of long bones from clinically based CT scans. A secondary aim is to apply the method to six long bones from a sample of three individuals. Periosteal and endosteal bone surfaces were segmented and used to calculate the characteristic cortical thickness, T c, at 1 mm increments along the bone axis. In the epiphyses where the value of T c fell below the scanner threshold, the endosteal bone layer was replaced using literature values projected inward from the periosteal surface. On average, 74.7 ± 7.4% of the bone geometry was above the scanner cut-off and was therefore derived from the CT scan data. The thickness measurement was also compared to experimental measurements of cadaveric bone and was found to predict T c with an error of 3.1%. This method presents a possible solution for the characterization of characteristic thickness along the length of the bone and may also aid in the development of orthopedic implant design and subject specific finite element models.